Semiologia da articulação temporomandibular - Marília Gerhardt de Oliveira (2007)
The base for the diagnosis of cause and effect is an agreement of the normal form and its relation with the function. It can still be considered that if it does not find a riot in the function, without a corresponding degree of alteration in the structure. Therefore, and for the fact of that a basic knowledge of the sthomatognatic system starts with the joint to temporomandibular (TMJ), it is basic the structural and anatomical study of this structure. The TMJ is a set of anatomical structures that, with the participation of special muscular groups, they make possible to the mandible to execute varied movements during the chew. Biaxial complex is classified in the synovial category, having had as component anatomical the articulate surfaces, the articulate disc, the capsules, the ligaments, beyond the synovial membranes. The articulate surfaces are formed by a surface of the head of the mandible and by a surface of the articulate part of the temporal bone. The situations will be presented all here that the TMJ can be involved as the Anatomy, Physiology, Histology, Pathology, Examinations, Diagnosis, Diagnosis for image, Riots, Trauma and the Treatment.